Struggle For Normal Life In Stephenie Meyer's Twilight Novel (2005): An Individual Psychological Approach - Wirimiarti, Alies, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S. M. Hum (2014)
The major problem of this study is; how is struggle for normal life reflected in Stephenie Meyer's Twilight novel (2005). The objective of this study is to analyze "Twilight" novel written by Stephenie Meyer based on the structural element of the novel and describe of struggle for normal life in Stephenie Meyer's Twilight novel (2005) based on individual psychological approach. In Twilight novel, the researcher uses qualitative method and individual psychological approach. The researcher also uses two of data sources; primary data source and secondary data source. The primary data source is novel of Twilight itself and the secondary sources are the are taken from some books, web sites, and also other matters which support this analysis. The results of the study shows, first is the structural elements of Twilight novel shows that the character and characterization, setting, plot, point of view, theme and style. The Twilight is simple fiction novel based on portion for structural elements. Second, Edward Cullen as the major character must conquer the obstacle of life after he arrives in gloomy Forks, Washington. He must knew everything about his girl-friend (Isabella Swan), Bella's family and friends, about the situation and the rules within at the Forks High School. And the last, he must struggle to keep of his girl-friend life from the hunters (sucks of human's blood).